2015
DOI: 10.1111/echo.13002
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Congenital Heart Diseases by Three‐Dimensional Ultrasound Using Spatiotemporal Image Correlation: Influence of Professional Experience

Abstract: We believe that STIC can be used as a tool to improve the cardiac screening examination of the fetus. Professional experience was the most important influence in the image quality of the STIC volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Furthermore, tools for ‘intelligent’ navigation are now available that generate automatically cardiac views, speeding up the examination and decreasing operator dependency. The major shortcoming of 4D sonography of the fetal heart is the relatively high rate of failure in acquiring volumes of good quality, which in many different studies was around 25%, when the examination was kept within the standard time frame of a mid‐trimester exam. Our study suggests that, using an electronic probe, volumes of diagnostic quality can be obtained realistically in nearly all patients, and that indeed 4D echocardiography may become the primary approach to the sonographic examination of the fetal heart.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Furthermore, tools for ‘intelligent’ navigation are now available that generate automatically cardiac views, speeding up the examination and decreasing operator dependency. The major shortcoming of 4D sonography of the fetal heart is the relatively high rate of failure in acquiring volumes of good quality, which in many different studies was around 25%, when the examination was kept within the standard time frame of a mid‐trimester exam. Our study suggests that, using an electronic probe, volumes of diagnostic quality can be obtained realistically in nearly all patients, and that indeed 4D echocardiography may become the primary approach to the sonographic examination of the fetal heart.…”
Section: Discussionmentioning
confidence: 83%
“…In 80% of cases the volumes were optimal, allowing in practice a complete echocardiogram, if one excludes the use of color or pulsed Doppler sonography. The advantages of 4D over traditional two‐dimensional sonography of the fetal heart have been outlined previously. Once an adequate volume has been acquired, the relevant sections can be conveniently obtained offline without the interference of fetal movements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…127 Moreover, investigators have reported the impact of experience, in which more experienced sonographers have: (1) a significantly higher success rate of STIC volume acquisition than those less experienced (88.4% versus 70.5%; P = .02) 36 ; (2) significantly less reported fetal movements interfering with STIC volume acquisition (expert versus beginners, 12% versus 62%; P < .05); and (3) fewer motion artifacts observed in STIC volumes than in those acquired by beginners (16% versus 42%; P < .05). 36 Recently, Novaes et al 129 reported that in normal fetuses, the proportion of STIC volumes considered adequate to demonstrate 5 cardiac views was higher for STIC "specialists" than "nonspecialists" (66.7% versus 36.2%; P < .001). The latter group comprised physicians without experience in volumetric sonography.…”
Section: Operator Training and Experiencementioning
confidence: 99%